Case Report: When Does Puberty Become Traumatic? - Tarazi-Sahab, Layla; El Husseini, Mayssa; Moro, Marie-Rose (Frontiers in Psychiatry, 2021)
Puberty, the last major transformation of childhood, provokes a physiological upheaval that can be traumatic and destabilizing. The body is a protective vessel and a containing reference for the child. Emotional security during childhood is derived from a sense of predictability and well-being. However, both nascent sexuality and burgeoning libido trigger unsettling changes in the psycho-affective and psycho-dynamic equilibrium of the adolescent. This article presents puberty as a potential trauma that needs to be absorbed gradually. When the traumatic experience that can be part of puberty is not considered, it may compromise the ability to establish trust in ongoing therapies with adolescents. At best, pubescent trauma can cause superficial issues inadaptation. At worst, this trauma can lead to pathological symptoms. This article is a qualitative study from a clinical case study of a teenager, who expressed her pubescent suffering through withdrawal and mutism. The study will also determine symptomatic indicators of pubescent trauma, such as the suddenness of the transformations in the body, breaches in a child’s sense of safety and ability to predict, feelings of helplessness, experiences of nonsense, loss of the assumption of invulnerability, an inability to turn to parents for help, and a lack of peer support.